Protecting Moroccan Cyberconsumers in the Field of Digital Products: Reform Perspectives in Light of Comparative Law - Soufyane EL HOMRANI; Mohamed BEN MARZOUG (International Journal of Scientific Research and Innovative Studies, 2026)
Digital products, being intangible and constantly evolving, pose a challenge to traditional consumer protection tools. Based on Moroccan Law No. 31-08 and the Code of Obligations and Contracts, this article demonstrates that the lack of a distinct legal classification and the inadequacy of warranty and evidentiary rules undermine effective remedies, particularly regarding update-related failures and software obsolescence. By contrast, the EU framework, built on Directives 2019/770 and 2019/771 and the modernisation of product liability, provides benchmarks for reform. The article suggests avenues for Moroccan law, focusing on clearer categories, time-based digital conformity, update obligations, and the facilitation of evidence for consumers. Keywords: cyberconsumer, digital products, conformity, updates, evidence. Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/655